Understanding technology adoption and use by healthcare proferssionals using models of technology acceptance and q-methodology - Ladan, Muhammad Awwal; Wharrad, Heather; Windle, Richard (2017)
This study explores the use of models of technology acceptance (TAM and UTAUT) to understand technology adoption and use among healthcare professionals (HCPs) in the clinical area in Sub-Saharan Africa (SSA). Six themes were developed from both models and this generated forty-six specific statements that explore those barriers and motivators to e-health adoption and use in clinical practice. Each HCP ranked each of the statements based on how they agree or disagree with the statement in order to identify a shared perspective using Q-methodology; a methodology that explores subjectivity. Thirty-six HCPs working in the clinical area in SSA participated in the study. Analysis was done using a Q-methodology dedicated software called the PQMethod 2.35. Four perspectives identifying the aspect(s) of the model the HCPs identify to influence their use of technology in their clinical practice. Keywords: Q-methodology, Technology-Acceptance-Model (TAM), Unified-Theory-of-Acceptance-and-Use-of-Technology (UTAUT), Healthcare professionals